2015
DOI: 10.1371/journal.pcbi.1004478
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Intra-specific Regulatory Networks in a Multipartite Bacterial Genome

Abstract: Reconstruction of the regulatory network is an important step in understanding how organisms control the expression of gene products and therefore phenotypes. Recent studies have pointed out the importance of regulatory network plasticity in bacterial adaptation and evolution. The evolution of such networks within and outside the species boundary is however still obscure. Sinorhizobium meliloti is an ideal species for such study, having three large replicons, many genomes available and a significant knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 77 publications
1
51
0
Order By: Relevance
“…An in silico regulon analysis predicted that most S. meliloti transcriptional factors regulate genes on the same replicon (147). However, a subset was predicted to regulate genes across multiple replicons, and there was a bias for chromosomal regulators to modulate chromid/megaplasmid genes compared to the number of chromid/megaplasmid regulators predicted to regulate chromosomal genes (147). Consistent with this, the cell cycle regulator CtrA and the symbiotic nitrogen fixation regulator FixJ regulate genes on all three replicons in S. meliloti while preferentially regulating genes on the same replicon that they are encoded on (148,149).…”
Section: Interreplicon Interactionsmentioning
confidence: 83%
“…An in silico regulon analysis predicted that most S. meliloti transcriptional factors regulate genes on the same replicon (147). However, a subset was predicted to regulate genes across multiple replicons, and there was a bias for chromosomal regulators to modulate chromid/megaplasmid genes compared to the number of chromid/megaplasmid regulators predicted to regulate chromosomal genes (147). Consistent with this, the cell cycle regulator CtrA and the symbiotic nitrogen fixation regulator FixJ regulate genes on all three replicons in S. meliloti while preferentially regulating genes on the same replicon that they are encoded on (148,149).…”
Section: Interreplicon Interactionsmentioning
confidence: 83%
“…As these biosensors are plasmid based, it is possible to transfer them into different bacterial backgrounds (e.g. mutant strains of R. leguminosarum or other species of bacteria), although their expression in heterologous hosts may be limited by regulatory elements (Galardini et al, 2015). Each of the 14 lux reporters was tested on 26 different sugars and polyols and/or on a set of 18 selected compounds (organic acids, amino acids, and plant metabolites) to establish the specificity of the induction of lux expression from each of the bioreporters (Table I; Supplemental Table S2).…”
Section: Solute Specificity Of Biosensorsmentioning
confidence: 99%
“…Based on this approach, we identified that S. meliloti 1021 (Sme) is a module that contains a high proportion of orthologs with the other modules, where genes related to cellular metabolic process, primary metabolic process, nitrogen compound metabolic process and organism substance metabolic process were identified. This result could be associated to the prevalence of genetic redundancy in this bacterium, an in particular to those genes involved in a variety of metabolic pathways, including central carbon metabolism, transport, and amino acid biosynthesis (diCenzo and Finan, 2015); and the number of genes with some regulatory mechanisms identified in one of the three replicons, and the function of regulated genes was found to be in accordance with the overall replicon functional signature: housekeeping functions for the chromosome, metabolism for the chromid, and symbiosis for the megaplasmid (Galardini et al, 2015).…”
Section: Metabolism and Similar Regulationmentioning
confidence: 96%